Respondenci wobec inwestycji w energię jądrową w Polsce. Wyniki i omówienie badań - Smolińska, Katarzyna; Przemieniecka, Agata (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The social protest against energy investments often postpones or completely blocks developments of many power stations in Poland. The problem concerns wind, water and coal power stations, but the most controversial is a setup of nuclear plant. Based on research carried out by the authors and CBOS, we try to answer the question, whether it is possible to get social agreement for establishing nuclear plant in Poland. Also, we try to show the potential behavior and social syndromes, in particular the NIMBY one.